2006
DOI: 10.1002/jbm.a.30787
|View full text |Cite
|
Sign up to set email alerts
|

Using single‐walled carbon nanotubes nonwoven films as scaffolds to enhance long‐term cell proliferation in vitro

Abstract: Carbon nanotubes have attracted intensive interests in biomedical research in recent years. In this study, a novel type of carbon nanotubes material so called nonwoven single-walled carbon nanotubes (SWNTs) with nanotopographic structure and macroscopic volume was used as cell growing scaffold. The morphology and surface chemistry of nonwoven SWNTs were observed and characterized through scanning electron microscopy and X-ray photoelectron spectroscopy, respectively. The cells were cultivated in nonwoven SWNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…111,112 It is also widely known that the presence of CNTs in the scaffold promotes cell adhesion. 62,[113][114][115] Jell et al performed experiments on polyurethane-CNT nanocomposite (a porous structure) and concluded that the amount of MWNT in the scaffold's structure altered the resulting foam's physical, mechanical, and surface properties, and also the osteoblast phenotype. 116 The surface roughness of CNT scaffolds was also found to influence the increase of osteoblastic cell differentiation and proliferation.…”
Section: -105mentioning
confidence: 99%
“…111,112 It is also widely known that the presence of CNTs in the scaffold promotes cell adhesion. 62,[113][114][115] Jell et al performed experiments on polyurethane-CNT nanocomposite (a porous structure) and concluded that the amount of MWNT in the scaffold's structure altered the resulting foam's physical, mechanical, and surface properties, and also the osteoblast phenotype. 116 The surface roughness of CNT scaffolds was also found to influence the increase of osteoblastic cell differentiation and proliferation.…”
Section: -105mentioning
confidence: 99%
“…The disorganized cytoplasm network shown in Fig. 3a, most likely composed of actin (Meng et al 2006), indicates that the cells have grown over and under each other. The membrane boundary between cells is difficult to discern within the network.…”
Section: Cells Grown On Control Substratesmentioning
confidence: 99%
“…Moreover, PSIS is a natural and completely absorbable biomaterial, while MWNT are nonabsorbable and underwent rapid, first-order clearance from the blood compartment via renal excretion, although the CNT has been proved to have little influence on cell proliferation within safe concentration by various study. [30][31][32] The interaction between MWNT and VEGF in our system is noncovalent, which is considered a favorable factor for efficient drug release. Our system is not perfect, but we deem it a meaningful attempt to improve the performance of natural biological material, and a more ideal carrier will be adapted to the sustained release system in the near future.…”
Section: Discussionmentioning
confidence: 99%